Keadilan Ekonomi Dalam Pemberian Upah Karyawan Batik Langit Makmur Untuk Meningkatkan Kesejahteraan: Perspektif Ekonomi Islam - Irmawati Atika Putri; Unun Roudlotul Janah (Niqosiya: Journal of Economics and Business Research, 2025)
Introduction: Workers' welfare is closely related to the wage system implemented by the company. Batik Langit Makmur, located in Genilangit Village, Poncol District, Magetan Regency, is a batik company that implements an equalization system in wage payments for all employees. Although the duties and responsibilities are different, each employee receives the same wage. Research Methods: This research uses a qualitative approach and a type of field research. Data was obtained through interviews, observations, and documentation. Results: The implementation of the payment of wages for Batik Langit Makmur Genilangit Magetan employees has reflected the principle of justice in the perspective of Islamic economics. The wage system implemented uses a fixed daily wage, with a transparent payment process and based on an initial agreement between employees and the company, as well as attention to the welfare of workers through bonuses, opportunities for worship and considering weather factors in batik production. The reason for the implementation of equalization in the payment of wages between Batik Langit Makmur employees aims to create a fair and equitable work environment and avoid gaps that can cause dissatisfaction among employees. Conclusion: The impact of equalization in wage payments on the welfare of Batik Langit Makmur workers has a positive impact on employees who previously did not have a fixed income. However, in the aspect of education and health, the wages received are still considered insufficient to meet the needs optimally.